Analisis Dinamika Kepribadian pada Tokoh Tara dalam Novel Katarsis Karya Anastasia Aemilia - Dina Aprilia Dewi Sofiana; Zahra Kautsa Syadida; Eva Dwi Kurniawan (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
The purpose of this study is to analyze the characteristics of the character Tara in the novel Katarsis by Anastasia Aemilia. The researcher uses Sigmund Freud's personality dynamics theory to examine Tara's traits that appear in Anastasia Aemilia's novel Katarsis. The work is a "thriller psychology" genre. The protagonist's involvement in a serial murder plot and the complex dynamics of the novel's female protagonist are points of contention. This research utilizes literary psychology methodology to conduct descriptive qualitative research. The findings show that the female protagonist in the novel exhibits tendencies of aggression and anxiety. Tara's destructive, hurtful and murderous actions characterize her aggressive tendencies. A negative affective state accompanied by bodily feelings is known as anxiety. On the other hand, Tara also has psychopathic behavior and has manipulative, antisocial and impulsive behavior.